Private Equity and Its Emergence in Orthopaedics. Issue 20 (15th October 2021) - Patel, Alpesh A.; Fernandez, Claire; Mazmudar, Aditya
Abstract : Private equity (PE) is increasing its role in healthcare financing and may be a source of strategic funding for orthopaedic practice groups. With acquisitions in other medical specialties such as dermatology and ophthalmology, PE works to increase operating efficiency and cut costs. Orthopaedic practices' access to revenue through ancillary services and ambulatory surgery centers, coupled with a growing, aging cohort, make them an attractive candidate for PE acquisition. However, careful consideration is warranted before surgeons enter these partnerships to ensure patient safety, and the quality of care is not compromised because PE works to increase the return on their investment.